A Study of Emotional Intelligence of Scheduled Caste Students In Relation to Academic Achievement at Secondary Level: Exploring the Interplay between Emotional Intelligence and Academic Success among Scheduled Caste Students at the Secondary Level (Journal of Advances and Scholarly Researches in Allied Education, 2014)
EmotionalIntelligence (EI) is a recent development in the area of cognitive(intelligence) as well as affective domain. Both the domains are overlapped inthe concept of Emotional Intelligence. The concept of EI implies that humansare both rational and emotional beings. They are exclusively neither rationalbeings nor emotional ones. Hence adapting to and coping with the newcomplexities of life are dependent on the integrative functioning of bothrational and emotional capacities.